Implementation of Holistic and Integrative Early Childhood Education Program in Serang - Rahmah, Miftah Fadhilah; Salianty, Syariah (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Young children in early childhood education benefit greatly from comprehensive and integrated services. Recognizing this, the government established a Presidential Regulation for Holistic Integrative Early Childhood Education Services. This approach emphasizes providing children with well-rounded care that addresses their diverse needs in a cohesive manner. This study focuses on understanding the implementation of the Holistic and Integrative Early Childhood Education program within a kindergarten in Serang City. Employing a descriptive qualitative methodology, the research collected data through interviews, observations, and documentation to explore the program's practices. Findings reveal that the Holistic Integrative Early Childhood Education program encompasses a wide range of services, including education, health, nutrition and care, parenting support, protection measures, and welfare initiatives. Educational activities are enriched through the use of diverse learning methods and resources. The school also prioritizes health, nutrition, and nursing services, fostering collaboration with local stakeholders in Serang City to ensure comprehensive care for the children.